(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article discusses the main factors of migration in a market economy, the global approach to migration, employment and the emergence of unemployment in the transition from a planned to a market economy, relations between the state of ethnic minorities and the preservation of national values, the modern nature of the movement and adaptation of the Central Asian population